Illegal wildlife trade: An analysis of carnivore products found in markets in Benin and Niger - Gerstenhaber, Chloé; Ipavec, Audrey; Lapeyre, Vincent; Plowman, Christian; Chabi-N’Diaye, Yekini; Tevoedjre, Félicia; Amoussa, Chérifou Adéyèmi; Siddo, Omar Soumana; Aboubacar, Hassane Abdou; Durant, Sarah M. (Global ecology and conservation, 2024)
West Africa is home to one of the largest protected area systems in Africa, the W-Arly- Pendjari (WAP) Complex, which provides a last refuge for many threatened carnivore species extirpated from most other protected areas in the region. However, rising global demand for wildlife products has increased concerns about the impacts of Illegal Wildlife Trade (IWT) on these species. To assess the extent of IWT, covert market surveys were conducted in Benin and Niger to identify wildlife products and derivatives coming from carnivore species (African civet, serval, caracal, lion, cheetah, leopard, and spotted hyena) suspected to be targeted by IWT. When possible, information about product origin was gathered to understand trading routes. Data were analysed to determine if products were available in markets due to their proximity to source populations or due to accessibility to trade and transport hubs. A variety of products from several threatened species, including multiple lion skins, were found in Benin and Niger. Products were found more frequently in markets near the WAP Complex and main trade and transport hubs. Sellers reported that a large majority of products originated from international trade, but some could also have been sourced from the WAP Complex. There was little evidence indicating that product availability was more affected by the distance to the WAP Complex than by the distance to international transport hubs, suggesting that trade was widespread across both countries. The study provides an evidence base and monitoring baselines to identify and assess interventions to address IWT and ultimately reduce illegal trafficking of wildlife. L’Afrique de l’Ouest abrite l'un des plus grands systèmes d’aires protégées d’Afrique, le complexe W-Arly-Pendjari (WAP), qui constitue le dernier refuge aux grands félins qui ont disparu de la plupart des autres zones protégées de la région. Cependant, l’augmentation de la demande mondiale de produits issus de la faune sauvage a suscité des inquiétudes quant à l’impact du commerce illégal sur ces espèces. Afin d’évaluer l’ampleur de ce commerce illégal, des enquêtes sous couverture ont été menées sur des marchés du Bénin et du Niger. L’objectif de ces enquêtes était d’identifier les produits et dérivés provenant d’espèces de carnivores (civette africaine, serval, caracal, lion, guépard, léopard et hyène tachetée) soupçonnées d'être ciblées par le commerce illégal. Lorsque cela a été possible, des informations sur leur provenance ont été recueillies afin de comprendre les itinéraires commerciaux. Les données ont été analysées pour déterminer si les produits étaient disponibles sur les marchés en raison de leur proximité avec les populations sources ou de l’accessibilité des centres de commerce et de transport. Une variété de produits provenant de plusieurs espèces menacées, y compris une grande quantité de peaux de lion, a été trouvée au Bénin et au Niger. Les rapports des vendeurs indiquent qu'une grande majorité des produits provient du commerce international, mais certains pourraient également provenir du Complexe WAP. Peu d'éléments indiquent que la disponibilité des produits est plus affectée par la distance au complexe WAP que par la distance aux centres de transport internationaux, ce qui suggère que le commerce est largement répandu dans les deux pays. Cette étude fournit les informations de base nécessaires pour identifier et évaluer les interventions visant à lutter contre le trafic illicite d'espèces sauvages et, à terme, le réduire.